PEREMAJAAN KAWASAN MAKAM KERKHOFF SEBAGAI OBJEK BERSEJARAH DI BANDA ACEH - Mirza Fuady (Diponegoro University, 2012)
In general, this article represent the early study about urban renewal and preservation in the area of Kerkhoff graveyard in Banda Aceh. The background of this study is the symptom which appear in this area, which is the existence of desire to conduct more new construction with better quality and modern but felt concerned about it could tarnish the existence of Kerkhoff as historic object which must be preserved. Research formulation of this study is the importance of revitalisation in the area of Kerkhoff graveyard which have been recognized as historic place and the need of urban renewal effort integrated with the concept of rehabilitation the quality and identity in the area of Kerkhoff graveyard. The objective of this study is to create the solution in the form of idea plan of urban renewal as recommendation. This qualitative research use the descriptive method systematically, factual and accurate about preserving historic object with the special approach in the form of historical aspect and building tipology.